Future S&T human resource requirements in the Philippines: A labor market analysis - Jose Ramon G. Albert; Ana Maria L. Tabunda; Carlos Primo C. David; Kris A. Francisco; Charlie S. Labina; Janet S. Cuenca; Jana Flor V. Vizmanos (Philippine Institute for Development Studies (PIDS), 2020)
As vibrant actors in the innovation ecosystem, the S&T human resources of any country are crucial in developing, adapting, and introducing technological innovations across various sectors in the economy. Given the massive disruptions in business models emerging from the increasing use of emerging technologies of the Fourth Industrial Revolution, we expect corresponding consequences in the labor market and the nature of work. The government needs to ascertain the actual conditions surrounding the cultivation of S&T human resources in the country. This study aims to describe the prevailing supply and demand conditions, patterns and recent trends regarding S&T human capital in the Philippines by xamining secondary data from various data sources. Overall, the results show that although the scientific workforce constitutes only a minute share of the total workforce, and that the variegated occupations across S&T do not have uniform growth potentials as regards employment, both the government and the private sector need to support most of S&T disciplines, especially in the wake of new tasks from emerging technologies of the fourth industrial revolution. Despite an increasing demand for S&T resources and indicators on employability prospects, many of the young do not pursue and persevere in Science, Technology, Engineering and Mathematics (STEM) careers. Government and the private sector should be incentivizing them toward STEM even as early as junior high school. Providing financial assistance or scholarships can be helpful, but this alone may not be enough to produce the needed pool of future S&T human resources. Government is advised to also gain insights on various factors that affect the supply of S&T workers to craft necessary policies for incentivizing S&T graduates to persevere in their disciplines, and actively participating in the economy. The future appears favorable for engineers given our current level of productivity, technology, and projected growth. In contrast, the economy may not be able to accommodate the increasing supply of workers with Computing/IT background, although some if not many of those with computing skills may be accommodated in new jobs. Still, it may be prudent to substantially invest in S&T human resources, and provide supporting mechanisms to make our S&T human resources agile and our innovation ecosystem flourish.
Keywords: 330; Science and Technology; human resources; innovation; labor market